(untitled) (Research, Society and Development, 2020)
In recent years, mycoses have become a serious public health problem, mainly due to the increase in the number of people with immunodeficiency, innate or acquired, and the appearance of multiresistant microorganisms due to the indiscriminate use of antibiotics. In order to minimize these problems, compounds containing the 1,2,4-oxadiazolic ring are the target of numerous pharmacological and toxicological studies aimed at developing new, more potent and selective antimicrobials. Thus, the present study aimed to evaluate the toxicological and antifungal potential of the compound 2-(3-phenyl-1,2,4-oxadiazol-5-yl)phenol. The synthesis of compound 2-(3-phenyl-1,2,4-oxadiazol-5-yl)phenol was carried out from the reaction between benzamidoxime and ethyl salicylate. Toxicological potential was evaluated using the microcustacean Artemia salina Leach. The evaluation of the antifungal potential was carried out against different strains of potentially pathogenic fungi, using the serial microdilution technique. After 24h of reaction, the compound 2-(3-phenyl-1,2,4-oxadiazol-5-yl)phenol was obtained with 72% yield, had a melting point of 159-160ºC and the 1H and 13C NMR data corroborate its structure. The compound showed low toxicity against the brine shrimp, with an LC50 of 565,100 μg/mL, while the Minimum Inhibitory Concentration and Minimum Fungicidal Concentration showed equal values of 4000 μg/mL for the fungus Rhizopus orizae. These results encourage other studies, since compound showed low toxicity and reduced spectrum of action, which favours the treatment of specific fungal infections.